2010
DOI: 10.1124/dmd.110.034090
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Affects Fluvastatin-Induced Hepatotoxicity and Myopathy in Rats

Abstract: ABSTRACT:Rats that consumed a high-fat and high-sucrose diet (HF diet) developed hepatic steatosis. Treatment of HF diet-fed rats with fluvastatin (8 mg/kg) was lethal, followed by an elevation in levels of plasma aspartate aminotransferase and creatine kinase activities and skeletal muscle toxicity. This study was conducted to determine whether nutritional status affects statin-induced adverse effects in rats. Fluvastatin treatment of rats fed the HF diet led to an increase in systemic exposure, suggesting al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
(57 reference statements)
1
7
0
Order By: Relevance
“…It has been reported that consumption of pectin or oat bran soluble fiber together with lovastatin reduces its absorption (Metzger et al, 2009), whereas alcohol intake does not affect the efficacy and safety of fluvastatin treatment (Smit et al, 1995). On the other hand, fluvastatin treatment in rats on high-fat and high-sucrose diet was lethal, suggesting that both altered statin metabolism and elimination increase plasma levels of aspartate aminotransferase and creatine kinase, resulting in skeletal muscle toxicity (Sugatani et al, 2010). Moreover, olive oil, consumed in a Mediterranean-style diet, can increase the cholesterollowering effect of simvastatin compared with sunflower oil.…”
Section: Statins and Cancer: Pros And Consmentioning
confidence: 99%
“…It has been reported that consumption of pectin or oat bran soluble fiber together with lovastatin reduces its absorption (Metzger et al, 2009), whereas alcohol intake does not affect the efficacy and safety of fluvastatin treatment (Smit et al, 1995). On the other hand, fluvastatin treatment in rats on high-fat and high-sucrose diet was lethal, suggesting that both altered statin metabolism and elimination increase plasma levels of aspartate aminotransferase and creatine kinase, resulting in skeletal muscle toxicity (Sugatani et al, 2010). Moreover, olive oil, consumed in a Mediterranean-style diet, can increase the cholesterollowering effect of simvastatin compared with sunflower oil.…”
Section: Statins and Cancer: Pros And Consmentioning
confidence: 99%
“…The observation may result from the fact that the portal plasma insulin levels in the HF group markedly increased compared to those in the SD group (Figure 3C). Since rats fed the HF diet and treated with fluvastatin at 8 mg/kg/day died within 2 weeks [20], we examined the effect of fluvastatin at 4 mg/kg/day ( per os ). Fluvastatin given at 4 mg/kg/day for 2 weeks, as a component of the diet, also suppressed serum triacylglycerol levels and hepatic triacylglycerol and total cholesterol levels, but not serum total cholesterol levels, in rats fed the HF diet (Figures 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Unexpectedly, an additive or synergistic effect of co-treatment on the suppression of elevated serum and liver total cholesterol levels was not found, while the suppression of elevated serum and liver triacylglycerol levels was slightly stronger than that by each individual treatment alone (Figures 1 and 2). In the previous study [20], we found the severe adverse effects of fluvastatin (8 mg/kg/day) in rats fed the HF diet. Preceding the elevation in serum creatine kinase levels and muscle damage in rats fed the HF diet containing fluvastatin (8 mg/kg/day), we have found that serum AST levels were elevated, but the increase in serum AST levels were not observed in rats fed the HF diet containing fluvastatin (4 mg/kg/day).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sugatani et al [2] used male, 6-weeks age Wistar rats to study whether nutritional status affects adverse effects of fluvastatin. Rats were fed with a standard diet (SD diet) [12.9% lipid, 60.4% carbohydrate, and 26.7% protein (kilojoules)] or high-fat and high-sucrose diet (HF diet) [23.9% lipid, 56.8% carbohydrate, and 19.3% protein (kilojoules)] for one week, administered fluvastatin with the diet for another 4, 8, or 14 days.…”
mentioning
confidence: 99%